Magnetic correlations between two Kondo impurities with two magnetic configurations: Narrow-band limit - Allub, Roberto Jose (Elsevier Science, 2013)
Fil: Allub, Roberto Jose. Comision Nacional de Energia Atomica. Gerencia del Area de Investigaciones y Aplicaciones no Nucleares. Gerencia de Fisica (CAB); Argentina